The outsiders : economic reform and informal labour in a developing economy - Marjit, Sugata, 1959-; Kar, Saibal (New Delhi ; Oxford : Oxford University Press, 2011)
This book provides a detailed theoretical overview and analytical understanding of informal labour markets in the context of economic reforms. Grounded in the neo-classical general equilibrium framework, it analyses the impact of deregulatory policies on the welfare of informal workers in a segmented labour market.
Includes bibliographical references and index.
Description based on print version record.
Keywords: Informal sector (Economics) -- Developing countries; Labor market -- Developing countries; Economic development -- Developing countries